Here's the question you clicked on:
octoberchick1011
How do I solve the system using elimination? Please explain & show your work! Thank you!!! (: -8 – 6x = -7y ½ = -x + ¾y
multiply the second equation by 6 then adding this to first equation will eliminate x then solve for y finally plug in this value of y into equation 1 and solve for x.
multiply no 2 by 6: 3 = -6x + 4.5y -8 = 6x - 7y (rearranging no. 1) add -5y = -2.5y can you continus from here?
** sorry its -5 = -2.5y
do u need any more help?
No thank you I got it from here! -- sorry for the late responce, I had to step away from the computer fro a sec! Thank you so much! (: